Plasma oscillations propagating along the magnetic field in the Uragan-2M torsatron - Skibenko, A.I.; Prokopenko, A.V.; Pinos, I.B. (Вопросы атомной науки и техники, 2013)
The spectral and correlation analysis were applied to study interferometry date measured in two toroidally spaced transverse sections. The oscillation frequency increase for higher magnetic field and decrease with density rising which cold be attributed with existance of Alfven eigenmodes. Calculated frequency values cold be higher that from spectral analysis. This may be due to presence of impurities in plasma. Спектральный и корреляционный анализы проведены для изучения интерференционных данных, изме- ренных в двух тороидально отстоящих сечениях. Частота колебаний растет с увеличением магнитного поля и уменьшается с ростом плотности. Это может характеризовать их как собственные альфвеновские моды. Вычисленные значения частоты больше, чем полученные из спектрального анализа. Это возможно из-за наличия в плазме примесей. Спектральний і кореляційний аналізи проведені для вивчення інтерференційних даних, виміряних у двох тороїдально віддалених перерізах. Частота коливань зростає зі збільшенням магнітного поля і зменшується з ростом густини. Це може характеризувати їх як власні альфвенівські моди. Обчисленні значення частоти перевищують одержані із спектрального аналізу. Це можливо за наявністю домішок у плазмі.